The Implementation of Course Review Horay Learning Model with Flip Chart Media to Improve Thematic Learning Outcomes of Elementary School Students - Inas Yustahari Yuni Awalia; Muh Ngali Zainal Makmun; Lutfi Fadilah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This study employs the Course Review Horay learning model with the use of flip chart media in an effort to enhance theme learning outcomes. The quantitative approach used in this study is of the quasi-experimental variety. This study uses a Course Review Horay learning model with flip chart media as its independent variable and student learning results as its dependent variable. In this study, 22 pupils were used as a sample. Observation, interviews, tests, surveys, and documentation were the methods employed to gather data. The steps of evaluating hypotheses and checking for normalcy make up the data analysis procedure. The paired sample t test (t test) yielded Sig. (2-tailed) 0.03 in the experimental class, according to the results of the hypothesis test. In contrast, the control class had a Sig. (2-tailed) of 0.01. The findings of the 2-tailed sig value can be compared with hypothesis testing if the sig (2-tiled) value is between 0.01 and 0.03. Assuming the 2 tailed sig value is greater than 0.05, the null hypothesis is rejected if it is less than 0.05. This demonstrates that the thematic learning outcomes of third graders at SD Negeri 1 Jaya Sakti are impacted by the implementation of the Course Review Horay Learning Model with the help of Flip chart. The normalcy test revealed that the Experiment class had significance values of 0.230 and 0.201 before and after the test, whereas the Control class had significance values of 0.200 and 0.205. If the p-value is less than 0.05, it can be inferred that the data follows a normal distribution.